Giant pandas : biology and conservation - Lindburg, Donald G., 1932-; Baragona, Karen, 1967- (University of California Press, 2004)
The slow resurgence in the wild population of giant pandas is one of the great success stories of conservation. This volume covers the research, local commitment & government involvement that made it possible, & includes papers by Chinese scientists whose work has not previously been available in English.